Taxonomy of Buenos Aires Capitular Elite Network, 1776-1810 - Larrosa, Juan M.C.; del Valle, Laura C. (AWARI, 2020)
We analyze structural properties and visualization of a historical-data-constructed social network of the families with members in the Cabildo (city council) of colonial Buenos Aires. The data was obtained through the review of birth, marriage, and death records kept in various institutions and expanded from online genealogical sources. We find structural properties and visual presentations and also a link centrality analysis that shows that ritual relationship represents an important glue that held together with the network.